Systematic Literature Review: Kebijakan Pemerintah terhadap Penyaluran Dana Bantuan Sosial Bagi Pelaku UMKM di Indonesia - Yunia Aprilia; Luluk Latifah; Iskandar Ritonga (Jurnal Kebijakan Pembangunan, 2022)
MSMEs are an essential pillar in the Indonesian economy with a significant contribution to the value of GDP and employment. The occurrence of the Covid 19 pandemic had a major impact on MSMEs in the form of a decrease in the value of trade and labor absorption. In order for MSMEs to survive, the Government provides program support, including social assistance for MSME actors. This study aims to determine the effectiveness of government policies in distributing social assistance for MSME actors in Indonesia and their solutions. With the SLR approach in journals published in 2020 and 2021, the results show that government policies on the distribution of social assistance are very influential because they can help with limited capital and save MSMEs from the threat of going out of business. However, it has not been effective due to the limited resources, both financially and with staff support. Hence, the inefficient bureaucratic system also contributes to the inaccurate targeting of aid recipients, resulting in the unequal distribution of aid and the large number of small entrepreneurs who have not been registered with the Cooperatives and SMEs Office. The solutions provided are adding staff and improving the bureaucratic structure, implementing a new formula to be used as a reference in inputting data on social assistance recipients, and collaboration between the central and regional governments to ensure the social assistance distribution runs effectively.